2018
DOI: 10.1177/1479164118758580
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in an animal model of polycystic ovary disease is aggravated by vitamin D deficiency: Vascular consequences

Abstract: Hyperandrogenic state in females is accompanied with metabolic syndrome, insulin resistance and vascular pathologies. A total of 67%-85% of hyperandrogenic women suffer also from vitamin D deficiency. We aimed to check a potential interplay between hyperandrogenism and vitamin D deficiency in producing insulin resistance and effects on coronary resistance arteries. Adolescent female rats were divided into four groups, 11-12 animals in each. Transdermal testosterone-treated and vehicle-treated animals were kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 24 publications
3
40
0
Order By: Relevance
“…On the other hand, in case of vitamin-D-dependency, the organ or tissue cannot adapt by receptor-upregulation to the concentration changes, so it will be sensitive and vulnerable to vitamin D deficiency. According to our previous results from animal experiments, small vessels from the heart and brain are vitamin-D-dependent tissues, because in extreme vitamin-D-deficient milieu, they go through major changes [ 18 , 19 , 23 , 37 , 42 ], but these alterations are depending on which region the vessels are originated from. Both vitamin D deficiency and toxicity can induce smaller carotid artery diameter and larger wall thickness in male Wistar rat models within 4 weeks [ 43 ].…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in case of vitamin-D-dependency, the organ or tissue cannot adapt by receptor-upregulation to the concentration changes, so it will be sensitive and vulnerable to vitamin D deficiency. According to our previous results from animal experiments, small vessels from the heart and brain are vitamin-D-dependent tissues, because in extreme vitamin-D-deficient milieu, they go through major changes [ 18 , 19 , 23 , 37 , 42 ], but these alterations are depending on which region the vessels are originated from. Both vitamin D deficiency and toxicity can induce smaller carotid artery diameter and larger wall thickness in male Wistar rat models within 4 weeks [ 43 ].…”
Section: Discussion Limitations and Strengthsmentioning
confidence: 99%
“…They were supplied with tap water and food ad libitum for the following 8 weeks. Vitamin D supplemented animals ( n = 11, served as “Control” group) were fed with conventional rat chow (SM Rat/mouse normal diet S8106-S011, Ssniff Spezialdiäten GmbH, Soest, Germany), which was supplemented with per os vitamin D (Vigantol, 20.000 IU/mL, Merck/Serono, Mumbai, India) to reach 300 IU/kgbw daily dose that can be considered for optimal vitamin D supply [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The presence of VDR in most of the tissues provides a mechanistic link between vitamin D deficiency and the pathophysiology of the disorders. Recently, increased VDR expression in the medial smooth muscle cells of the coronary artery was observed in vitamin D deficient rats [ 22 ]. Although the exact mechanism is still unclear, the report suggests that the insulin- mediated coronary arteriole relaxation was affected in the absence of vitamin D and this correlates with increased expression of VDR.…”
Section: Discussionmentioning
confidence: 99%
“…About 67 to 85% of hyperandrogenic women also suffer from vitamin D deficiency. In a testosterone‐induced PCOS rat model, vitamin D deficiency aggravated IR (Hadjadj et al, ). Moreover, several longitudinal observational studies have shown that vitamin D‐deficient subjects have a higher risk of developing type 2 diabetes (Knekt et al, ; Pittas, Sun, Manson, Dawson‐Hughes, & Hu, ).…”
Section: Discussionmentioning
confidence: 99%